2015
DOI: 10.1116/1.4917495
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aliovalent impurities on the resistance switching characteristics of sputtered hafnium oxide films

Abstract: In this work, the effects of various aliovalent impurities on the resistance switching characteristics of hafnium oxide (HfO2) films were investigated in conjunction with analyses of chemical bonding states and film microstructure. HfO2 films were cosputtered with magnesium, aluminum, and niobium by reactive DC magnetron sputtering. Doping with aliovalent elements caused the nonlattice oxygen concentration of HfO2 to increase and grain size to decrease. Also, post-thermal annealing induced a further increase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…). Lee et al 10 reported that the doping of aliovalent ions (e.g., Al 3+ , Mg 2+ , Nb 5+ , etc.) into HfO 2 resulted in an increase in the nonlattice oxygen (NLO) concentration and a reduction of the size of the grain boundary.…”
Section: ••mentioning
confidence: 99%
See 1 more Smart Citation
“…). Lee et al 10 reported that the doping of aliovalent ions (e.g., Al 3+ , Mg 2+ , Nb 5+ , etc.) into HfO 2 resulted in an increase in the nonlattice oxygen (NLO) concentration and a reduction of the size of the grain boundary.…”
Section: ••mentioning
confidence: 99%
“…According to Lanza et al., RS behavior could be effectively modified by the formation and migration of oxygen vacancies (V O •• ). Lee et al reported that the doping of aliovalent ions (e.g., Al 3+ , Mg 2+ , Nb 5+ , etc.) into HfO 2 resulted in an increase in the nonlattice oxygen (NLO) concentration and a reduction of the size of the grain boundary.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that regulation of the rate of V o migration and the defect states of CFs enhance the controllability of the RS operation. Lee et al investigated the doping effects of various aliovalent ions (Mg 2+ , Al 3+ , Nb +5 ) into HfO 2 on RS characteristics [ 197 ]. Doping with aliovalent elements caused an increase in the nonlattice oxygen concentration and a reduction in the grain size in HfO 2 .…”
Section: Effect Of V O In Hfo 2 ...mentioning
confidence: 99%
“…[28][29][30] Studies have shown that aliovalent ion doping via sputtering into HfO xbased devices have better uniformity of the low resistance state (LRS) and high resistance state (HRS) due to increased concentration of non-lattice oxygen. 28,31 Moreover, there have been previous studies on the impact of titanium doping in HfO x memristors with the active materials synthesized via sputtering. For example, devices containing a sputtered HfO x /TiO x / HfO x /TiO x multilayer (ML) have shown multilevel capability and analog reset characteristics.…”
Section: Introductionmentioning
confidence: 99%